Interface-enhanced conductivities in surfactant-mediated, solution-grown ionic crystalline complexes - Chen, Jihua; Keum, Jong; Wang, Yangyang; Wang, Hanyu; Lokitz, Bradley; Yang, Guang; Yuan, Yue; Kumar, Rajeev; Advincula, Rigoberto (Frontiers in Nanotechnology, 2023)
Renewable energy is increasingly relying on optimized electrolytes and interfaces. In this work, Tween 20 and sodium chloride are selected as a model system to reveal the effect of surfactants on salt crystallization in the context of ion conductivity and interface optimization. At a varied crystallization speed and mix ratio, it is demonstrated that the resultant ion , solution-grown, ionic crystalline complexes can achieve a highly tunable ion transport with a controllable crystalline interface. X-ray diffraction results rule out the possibility of polymorphism in the NaCl/ Tween 20 systems, which further supports the importance of an optimized crystalline network for optimizing permittivity or ionic conductivity.Raman mapping and machine learning techniques are used to perform semantic segmentation on highly heterogeneous NaCl/ Tween 20 complexes. Furthermore, FTIR measurements demonstrate that inter-and intra-molecular interactions play critical roles in forming these crystals. This work lays a foundation towards future optimization of such complex ion systems for a specific salt or crystallization-modifier in energy storage or ion transport applications.